IEO Annual Report 2015. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2015)
The twelfth Annual Report of the Independent Evaluation Office (IEO) describes activities during financial year 2015 (May 1, 2014-April 30, 2015). During the financial year, the IEO completed an evaluation of the IMF response to the global financial and economic crisis. It also issued two reports updating three past evaluations: The IMF's Approach to Capital Account Liberalization: Revisiting the 2005 IEO Evaluation; and Revisiting the IEO Evaluations of the IMF's Role in Poverty Reduction Strategy Papers (PRSP) and the Poverty Reduction and Growth Facility (PRGF) (2004) and the IEO Evaluation of IMF and Aid to Sub-Saharan Africa (2007). In addition, the Executive Board discussed the IEO evaluation of Recurring Issues from a Decade of Evaluation: Lessons for the IMF, which was issued to the Board in FY2014. The paper reports on the IEO budget and outreach efforts in the financial year. This paper also summarizes the evaluations on Recurring Issues and the IMF Response to the Financial and Economic Crisis, the Board discussions of these evaluations, and the two updates of past evaluations. It also discusses follow-up on IEO evaluations and addresses ongoing evaluations and the IEO work program going forward. A table lists the IEO evaluations and evaluation updates completed or in progress.